2011
DOI: 10.1002/hed.21661
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of annexin A2 downregulation in oral squamous cell carcinoma

Abstract: The reduction of ANXA2 expression in poorly differentiated tumors is expected to result in a loss of function aimed at the coordination of membrane signaling enzyme complexes. The consequences may manifest as an alteration of epithelial tissue growth and remodeling which eventually exert an influence on tumor progression and metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 68 publications
1
23
0
1
Order By: Relevance
“…Previous research has shown that ANXA2 over-expression is correlated with poor prognosis of human gastric carcinoma [39], conventional renal cell carcinoma [40], nonsmall cell lung cancer [11,41], esophageal squamous cell carcinoma [42], urothelial carcinoma [43], multiple myeloma [44], and colorectal cancer [12] and predicts rapid recurrence after surgery of endometrial cancer [45] and in pancreatic cancer patients undergoing gemcitabine-adjuvant chemotherapy [46]. ANXA2 down-regulation is associated with recurrence and poor prognosis of prostate cancer [47] and oral squamous cell carcinoma [48]. However, although dysregulation of ANXA2 expression predicts adverse prognosis of patients with a wide variety of malignant tumors according to a systematic review and meta-analysis [49], there is increasing evidence that ANXA2 is a differential diagnostic tissue and serum marker for HCC [13]; the relationship between ANXA2 expression and prognosis of HCC patients has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that ANXA2 over-expression is correlated with poor prognosis of human gastric carcinoma [39], conventional renal cell carcinoma [40], nonsmall cell lung cancer [11,41], esophageal squamous cell carcinoma [42], urothelial carcinoma [43], multiple myeloma [44], and colorectal cancer [12] and predicts rapid recurrence after surgery of endometrial cancer [45] and in pancreatic cancer patients undergoing gemcitabine-adjuvant chemotherapy [46]. ANXA2 down-regulation is associated with recurrence and poor prognosis of prostate cancer [47] and oral squamous cell carcinoma [48]. However, although dysregulation of ANXA2 expression predicts adverse prognosis of patients with a wide variety of malignant tumors according to a systematic review and meta-analysis [49], there is increasing evidence that ANXA2 is a differential diagnostic tissue and serum marker for HCC [13]; the relationship between ANXA2 expression and prognosis of HCC patients has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…In some other malignancies, such as laryngeal and squamous cell carcinoma (46), head and neck dysplasia (47), and osteosarcoma (48), ANXA2 is downregulated and its absence is correlated with poorly-differentiated tumors and with poor prognosis. When up-regulated, ANXA2 functions as a co-receptor for plasminogen, tPA and pro-cathepsin B and promotes the conversion of plasminogen into plasmin, which is required for invasion, metastasis and angiogenesis (10, 41).…”
Section: Discussionmentioning
confidence: 99%
“…A2 and a related A2-binding “receptor” has been reported to promote myeloma cell adhesion and growth in the bone marrow [102]. On the other hand, A2 expression in oral squamous cell carcinoma [103] or sinonasal adenocarcinoma [104] was found to be inversely related to histopathologic grade. These studies suggest that expression levels of A2 may have prognostic value in malignancy, but would need to be validated for each specific tumor.…”
Section: Lessons From the Clinicmentioning
confidence: 99%